The effect of Aloe vera bioactive and anthraquinone on the performance of laying hens - Pasaribu, Tiurma; Sinurat, A.P; Rakhman, Susana I.W (Indonesian Animal Sciences Society, 2005)
An experiment was conducted to study the use of Aloe vera bioactives as feed additives on the performances of laying hens. The Aloe vera bioactives was prepared as the dry gel (DG) and semi liquid gel (SLG). The Aloe vera was suplemented into the diets with concentration of equal to 0.5 and 1.0 g DG/kg diets. Diets contained commercial anthraquinone, a bioactive compound of Aloe vera with doses equal to 0.5 g DG and 1.0 dg/kg were also prepared. Diets were compared to control diets containing with and without antibiotic. Two hundred of fifty six laying hens strain Isa Brown aged 19 weeks were used for the experiment. Each treatment had 8 replicates with 4 hens in each replicate. The treatments were carried out for 30 weeks and parameters measured were egg production (% hen day/HD), egg weight, feed conversion ratio (FCR), feed consumption, egg quality, and mortality. Results showed that feed consumption was not significantly different (P>0.05), however DG 1.0 g/kg and anthraquinone 0.5 g/kg tended to decrease the feed consumption. Egg production was not significantly affected by antibiotic, DG, SLG, or anthraquinone (0.5 g/kg), but anthraquinone 1.0 g/kg had more egg production than control. Higher concentration of DG, SLG, and anthraquinone 1.0 g/kg gave better FCR than those of lower dosage (0.5 g/kg). Haugh unit was not affected by the treatment while yolk weight, egg shell and shell weight was significantly decreased by anthraquinone 0.5 g/kg (P<0.05). Mortality from all treatments was only 1.6%. It was concluded that treated by anthraquinone was better than that by Aloe vera, however, they were not significantly different. For the healthy reason, the use of Aloe vera is more saver than the use of anthraquinone. Â Â Key Words: Bioactives, Productivity, Layer